OPTIMALISASI PERLINDUNGAN HUKUM INDIKASI GEOGRAFIS TERHADAP PRODUK POTENSI INDIKASI GEOGRAFIS TERDAFTAR DAN TIDAK TERDAFTAR - , Al Ridho Setiawan, SH; , Prof. M. Hawin, S.H., LL. M., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Laws and regulations which are drafted beyond the interests of society are bound to fail in their implementation. The legal protection of Geographical Indications (GI) in Indonesia is provided for under Law Number 15 Year 2001 on Marks, and Government Regulation Number 51 Year 2007 on Geographical Indications (PP 51/2007) as the implementing regulation of the former. Although GI regulations in Indonesia comply with international standards and PP 51/2007 has been in force for littel years, their implementation is not yet optimally. This raises the question, why has it not been optimally? It is caused many factors related to the optimization of the law that has not been done. To know geographical indication protection in Indonesia, and also legal effort which conducted by a goverment to push the growing of geographical indication to geographical indication potency product in Indonesia, the researh method used is yuridis normatif. Based research result, that geographical indication protection in Indonesia cannot push the growing of geographical indication protection to geographical indication local production indonesia. Because legal fundament of geographical indication in Indonesia still joint forces with the UU Merek and only consisted of some articles. That articles also oppose against the articles about brand at UU Merek, so that make the regulation about geographical indication not clear. PP Indikasi geografis also only repeat the existing order in UU Merek. Unclear of regulation about geographical indication make geographical indication potency product in Indonesia not in optimal protection. Legal effort which can be conducted by government to push the growing of geographical indication protection to geographical indication potency productin Indonesia are the government make regulation about geographical indication itself (UU Indikasi Geografis). Later, make Geographical Indocation Directoratein Kementrian Hukum dan HAM Republic Indonesia. Local government must be active to make the database of geographical indication potency product in their area and make regulation to protect the geographical indication potency productin their area.